2015
DOI: 10.1002/anie.201506955
|View full text |Cite
|
Sign up to set email alerts
|

Turning Peptide Sequences into Ribbon Foldamers by a Straightforward Multicyclization Reaction

Abstract: The conformational control of molecular scaffolds allows the display of functional groups in defined spatial arrangement. This is of considerable interest for developing fundamental and applied systems in both the fields of biology and material sciences. Peptides afford a large diversity of functional groups, and peptide synthetic routes are very attractive and accessible. However, most short peptides do not possess well-defined secondary structures. Herein, we developed a simple strategy for converting peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…No chemical shift variation was observed at concentrationsf rom 1-10 mm, which suggested that no peptide self-association occurred under the analytical conditions. [19] Once again, this result supported the idea that the ribbon structure was governed by each preorganized a/(R)-ATC C 9/12 turn. Such strong NH deshielding (d > 9ppm) was formally related to formation of the typical C 9 -hydrogenb onds that surrounded the ATCresidues.…”
Section: Resultssupporting
confidence: 66%
“…No chemical shift variation was observed at concentrationsf rom 1-10 mm, which suggested that no peptide self-association occurred under the analytical conditions. [19] Once again, this result supported the idea that the ribbon structure was governed by each preorganized a/(R)-ATC C 9/12 turn. Such strong NH deshielding (d > 9ppm) was formally related to formation of the typical C 9 -hydrogenb onds that surrounded the ATCresidues.…”
Section: Resultssupporting
confidence: 66%
“…The formation of C 9 ribbon structures have been investigated in the homo‐oligomers of cis‐γ‐amino‐L‐proline as well as β,β‐disubstituted‐γ‐amino acid, gabapentin (Gpn) . β‐bend ribbon conformation has been reported in α‐amino‐γ‐lactam‐based foldamers . Recently, we have reported the ribbon structure involving C 10 and C 12 intramolecular hydrogen bonds in a tetrapeptide Boc‐Pro‐Aib‐Gpn‐Pro‐NHMe .…”
Section: Figurementioning
confidence: 99%
“…[13] Treatment with sodium hydride deprotonates the amide backbone, cyclizing to the Agl via a 5-exo-tet cyclization. [13] These dipeptide lactams were then utilized in solid and solution phase peptide synthesis. Since its introduction the Freidinger lactam has been incorperated into numerous biologically relevant peptide systems.…”
mentioning
confidence: 99%